Fused tetraphenylethylene–triphenylamine as an efficient hole transporting material in perovskite solar cells. Issue 21 (17th February 2020) - Zhang, Xianfu; Zhou, Zi'an; Ma, Shuang; Wu, Gao; Liu, Xuepeng; Mateen, Muhammad; Ghadari, Rahim; Wu, Yunzhao; Ding, Yong; Cai, Molang; Dai, Songyuan
Abstract : A new facile fused tetraphenylethylene–triphenylamine hole transporting material has been developed, which shows obviously higher performance than the non-fused counterpart in perovskite solar cells. Abstract : A fused tetraphenylethylene-based hole transporting material shows higher power conversion efficiency and better stability compared with its non-fused counterpart, and the former molecule even outperforms the conventional spiro-OMeTAD.